Synthesis of 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans relationships - Edwards, Alison A.; Sanjayan, Gangadhar J.; Hachisu, Shuji; Soengas, Raquel; Stewart, Alistair; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Templated tetrahydrofuran-based gamma-azido esters were prepared with the C-2 and C-4 functionalities in cis and trans relative configurations. This was achieved by ring contraction of the suitably protected 2-O-triflates of pentono-1,5-lactones (D-ribose and L-arabinose) with subsequent introduction of the azide via the 4-O-triflate. Access to a corresponding beta-azido ester was achieved in good yield. Little elimination product was observed by introduction of the azide via the 3-O-triflate. These azido esters are scaffolds. which may be predisposed to adopt secondary structural motifs, for example. for use as peptidomimetics; they may also be utilised for the preparation of stereodiverse compound libraries. (c) 2006 Elsevier Ltd All rights reserved.
Keywords: gamma amino acids; Peptidomimetics; scaffolds; sugar amino acids